Phytochemical Screening, Antioxidant and Cytotoxic Activities of Ethyl Acetate Extract of Calotropis gigantea Flower - Irwan, Irwan; Muhammad, Muhammad; Ayu laisni, Yasinia; Putri, Nissa Aulia (Universitas Andalas, 2025)
The investigation of phytochemical constituents and biological activities of natural extracts holds considerable potential in pharmacological research. Bioactive components derived from plants are often utilized in the development of novel therapeutic agents. The present study aimed to evaluate the phytochemical profile, antioxidant activity, and cytotoxic potential of Calotropis gigantea flower extract. The extraction was carried out using ethyl acetate as the solvent through maceration for 72 hours. Antioxidant activity was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, while cytotoxic activity was determined by the Brine Shrimp Lethality Test (BSLT). The ethyl acetate extract was found to contain alkaloids, flavonoids, tannins, and glycosides. It exhibited weak antioxidant activity (IC₅₀ = 329.74 mg/L) and moderate cytotoxic activity (LC₅₀ = 189.88 mg/L). These findings indicate that C. gigantea flowers possess diverse secondary metabolites with potential as antioxidant and anticancer properties.